2005
DOI: 10.1267/ahc.38.381
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo and In Vitro Immunohistochemical Study of Integrin Alpha Subunit Localization in the Rat Anterior Pituitary

Abstract: Different types of integrin alpha subunit were investigated immunohistochemically to determine the relationship between the cell adhesion molecule and the local morphology of the rat anterior pituitary using anterior pituitary tissues and primary cultured cells. Alpha 3 subunit was shown to be the main integrin subunit in the anterior pituitary. In vitro, immunoreactions of 3 subunit appeared mainly surrounding cell clusters. The distribution roughly overlapped with immunoreaction of laminin, while it was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We are the first to note that FS cells expressed integrin-a1, -a3, -a6, and -b1 (Fig. 7A); it was previously reported that integrin a5 was expressed in anterior pituitary cells in vivo and in vitro (Horacek et al 1994, Kikuchi et al 2005. Integrins comprise an a-and a b-subunit, which form a heterodimer.…”
Section: Discussionmentioning
confidence: 50%
“…We are the first to note that FS cells expressed integrin-a1, -a3, -a6, and -b1 (Fig. 7A); it was previously reported that integrin a5 was expressed in anterior pituitary cells in vivo and in vitro (Horacek et al 1994, Kikuchi et al 2005. Integrins comprise an a-and a b-subunit, which form a heterodimer.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast to other tissues, the specific laminin isoforms expressed in the anterior pituitary have not been identified, although several studies have confirmed the presence of laminin protein in this gland [ 10 , 11 , 13 , 19 ]. In the present study, we used RT-PCR to identify laminin chains expressed in the anterior pituitary.…”
Section: Introductionmentioning
confidence: 99%
“…Cultured cells were fixed with 4% paraformaldehyde in 25 mM phosphate buffer (pH 7.4) for 30 min at room temperature. The procedure for immunostaining was essentially the same as in Kikuchi et al , 2005 [ 8 ]. Primary antibodies used in experiments were rabbit anti-rat growth hormone (GH; Dr. K. Wakabayashi, Gunma University, Gunma, Japan, dilution of 1:12,800), anti-ovine luteinizing hormone (LH) β subunit (Dr. K. Wakabayashi, dilution of 1:12,800), anti-rat prolactin (NIH, Bethesda, MD, USA, dilution of 1:12,800), anti-rat thyroid-stimulating hormone (TSH) β subunit (NIH, dilution of 1:3,200), anti-porcine adrenocorticotrophic hormone 1–39 (ACTH; Dr. Nakamura, Hokkaido University, Hokkaido, Japan, dilution of 1:3,200), and anti-S100B protein (DAKO, Glostrup, Denmark, dilution of 1:500).…”
Section: Methodsmentioning
confidence: 99%